Herpes zoster in an immunocompetent infant with a history of varicella in early infancy and after a minor injury - case report and literature review - Dimić Jovana S. (Serbian Medical Society, 2021)
Introduction. Chickenpox is a common pediatric disease, while herpes zoster (HZ) is rare among children, especially among infants. HZ in infancy may appear after intrauterine or postnatal infection with varicella-zoster virus (VZV). We report on a case of HZ in an immunocompetent infant who had a history of chickenpox in early infancy. Case outline. A seven-month-old male infant was presented with skin changes in the left T1 and T2 dermatomes. Skin changes appeared eight days after the infant had a mild left-arm traction injury. The patient’s medical history revealed that he had a mild form of chickenpox at the age of three and a half months. After the clinical diagnosis of HZ was made, he was treated with oral acyclovir 20 mg/kg every six hours for five days and had complete recovery without any sequelae. Conclusion. Risk factors for pediatric HZ are immunosuppression and chickenpox during the first year of life. Local trauma is a reported risk for VZV reactivation among adults. To our best knowledge, our case is the first reported pediatric case in which the injury of the left arm precedes HZ appearance. Routine vaccination against chickenpox may be an important preventive measure because herd immunity will protect infants and immunocompromised children from getting chickenpox and thus HZ.